ANTARA KEDAULATAN PENGGUNA VERSUS PENGEBIRIAN KEBEBASAN INDIVIDU DALAM ERA MEDIA BARU - Novalia Agung Wardjito Ardhoyo (Jurnal Pustaka Komunikasi, 2020)
The number of internet users on various digital platforms in Indonesia is continuing increase. This is supported by the presence of smartphones and an easy to getting internet access. This condition also encourages the presence of various digital platforms in the form of applications. And without a registration fee increasing the users of the platform. But without realizing it, actually the users of various digital platforms become unpaid laborers. They also provide capital injections for the media kapitalism in the form of valuable data stores. The review in this paper uses a political economy perspective, aims to give some understanding the main issues related to new media audiences through describing a holistic picture about the dynamics of capitalism exploitation in social media platforms. The data needed in the analysis of this research was obtained through documentation studies. Furthermore, the analysis was carried out within a descriptive analysis framework, so the qualitative approach becomes the choice of method in this study. From the results of the study, it can be concluded that media capitalism has transformed. They are accommodating the users of various new digital media platforms, such as social media, online news sites, etc by stimulating them to always actively use it. The capitalists with their various transformations also take public data to be exchanged into profitable commodities.